Clinical Presentation Of Gastroesophageal Reflux Among Children With Chronic Constipation: Gastroesophageal Reflux Among Children with Chronic Constipation - Hussain, Amna; Hashir, Zaigham; Gohar Shah, Bushra; Farrukh, Riffat; Masood, Shaheen (Pakistan BioMedical Journal, 2022)
The gastro-esophageal reflux disease is the type of gastrointestinal disorder which is very common in children. To evaluate the overlap and correlation between different gastrointestinal track disorders different epidemiological studies are conducted. The chronic constipation and gastroesophageal reflux are the functional disorder of gastrointestinal (GI) track with the significant correlation. Objective: The purpose of the study was to elaborate the relationship between the very common and functional disorders of the gastrointestinal (GI) track; the gastroesophageal reflux and the functional constipation. Methods: Those patients who referred to pediatric gastroenterology department of hospital were included in the study. The children were diagnosed with functional constipation. For the diagnosis of FC the Rome III criteria was applied. Two groups were established. There were 34 number of patients diagnosed with FC in the experimental group, while 36 children suspicion of GERD disease were placed in control group. Results: The mean age of the children referred to the pediatric gastroenterology lab was observed to be 8 years. Out of 34 patients included in the experimental group the 15 were male and other 29 were female. Similarly, out of the 36 patients included in the control group the 16 were males and other 16 were females. The 24 months was observed as the mean duration of functional constipation. The 50% were experiencing hiccups in the experimental group, while 22% in the control group. The 75% patients in the control group suffering from chronic cough, while regurgitation was reported in other 72%. The 50% in the experimental group experienced belching. Coughing and regurgitation were seen in about 47% patients. Conclusion: The one of the most considered factors in treatment and monitoring of chronic constipation is functional gastrointestinal disorder. The symptoms of gastroesophageal reflux can be improved by treating chronic constipation.